(untitled) (The Science Post, 2026)
The voluntary carbon market (VCM) serves as a critical mechanism for mobilizing private climate finance, yet its credibility remains undermined by systemic challenges including opaque transaction records, inefficient pricing mechanisms, and the persistent risk of double-counting—where multiple stakeholders erroneously claim the same carbon credit. This study proposes a decentralized consortium blockchain architecture that addresses these limitations through automated verification and settlement of voluntary carbon credits. The proposed system employs Hyperledger Fabric as the foundational permissioned blockchain, integrating tokenization with unique cryptographic identifiers to ensure each credit maintains a verifiable, immutable lifecycle from issuance to retirement. Smart contracts automate compliance validation, implement a sequential double auction mechanism for efficient price discovery, and execute settlement upon verification completion. The architecture was validated through three scenario-based simulations under dynamic market conditions, achieving 89.4% transaction settlement accuracy and demonstrating consistent sub-five-second latency for credit verification. Results confirm the system effectively mitigates double-counting risks through cryptographic provenance tracking, while the automated settlement mechanism reduces transaction completion time by 73% compared to traditional manual verification processes. This research contributes a replicable framework for blockchain-enabled carbon market infrastructure, with practical implications for policymakers, registries, and market participants seeking enhanced transparency and operational efficiency in voluntary carbon trading.